Adenine nucleotide translocase family: Four isoforms for apoptosis modulation in cancer - Brenner, C.; Subramaniam, K.; Pertuiset, C.; Pervaiz, Shazib (Nature Publishing Group, 2011)
Mitochondria have important functions in mammalian cells as the energy powerhouse and integrators of the mitochondrial pathway of apoptosis. The adenine nucleotide translocase (ANT) is a family of proteins involved in cell death pathways that perform distinctly opposite functions to regulate cell fate decisions. On the one hand, ANT catalyzes the adenosine triphosphate export from the mitochondrial matrix to the intermembrane space with the concomitant import of ADP from the intermembrane space to the matrix. On the other hand, during periods of stress, ANT could function as a lethal pore and trigger the process of mitochondrial membrane permeabilization, which leads irreversibly to cell death. In human, ANT is encoded by four homologous genes, whose expression is not only tissue specific, but also varies according to the pathophysiological state of the cell. Recent evidence revealed a differential role of the ANT isoforms in apoptosis and a deregulation of their expression in cancer. In this review, we introduce the current knowledge of ANT in apoptosis and cancer cells and propose a novel classification of ANT isoforms. © 2011 Macmillan Publishers Limited All rights reserved.